The right to health in Colombia : a look at its application as a fundamental human right in Colombia and in the inter-American system for the protection of human rights - Araque Ortiz, Margy Geraldine (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article identifies the orbit of action and legal protection that has been addressed for the right to health in the field of the Inter-American System for the Protection of Human Rights, as well as in the constitutional, legal and jurisprudential scenario in the Colombian case, whose purpose It lies in establishing the conceptual and interpretative scope of the figure of the transmutation of the right to health, from the conventional and jurisprudential spheres, thus elucidating the evolution of this right from its character and benefit nature, to the incorporation of its fundamental content , autonomous, welfare and immediate compliance.